Nonlinear Relationship Between Systemic Immune-Inflammation and Hepatic Steatosis: A Population-Based Study in China - Zhao J; Yu L; Sun K; Wang Y; Xie F (Dove Medical Press, 2024)
Jing Zhao,* Li Yu,* Kangyun Sun, Yun Wang, Fangfei Xie Physical Examination Center, The Affiliated Suzhou Hospital of Nanjing Medical University, Suzhou Municipal Hospital, Gusu School, Nanjing Medical University, Suzhou, Jiangsu, People's Republic of China*These authors contributed equally to this workCorrespondence: Fangfei Xie; Yun Wang, The Affiliated Suzhou Hospital of Nanjing Medical University, Suzhou Municipal Hospital, Gusu School, Nanjing Medical University, 242 Guangji Road, Suzhou, Jiangsu, 215008, People's Republic of China, Tel +86 - 13913186601 ; +86 - 18913151605, Email fangfeixie@hotmail.com; 714388761@qq.comBackground: Studies on the associations between Systemic Immune-Inflammation (SII) and hepatic steatosis in China are still lacking. It is necessary to clarify the relationship between SII and hepatic steatosis in the Chinese population.Methods: This study was conducted from January 2022 to December 2022. A total of 37,095 participants were enrolled, among them, with 20,709 (55.83%) being males, and 16,386 (44.17%) being females. Physical and biochemical indicators were measured during a morning health examination after the examinees had fasted overnight. Diagnoses of hepatic steatosis were determined using an ultrasound test in accordance with the Chinese Guideline. Analysis of variance and chi-square tests were used to analyze the association between SII and hepatic steatosis. Stratification analyses were conducted based on age, gender, and obese status. Restricted cubic spline regression was also performed to explore the shapes of associations between SII and hepatic steatosis.Results: The average age of the 37,095 participants was 44.78 years old, with those with hepatic steatosis (11,599 (31.27%)) averaging 47.06 years old and those (25,496 (68.73%)) in the control group averaging 43.73 years old. SII was positively associated with hepatic steatosis. This association remained significant after conducting stratification analysis by age and gender. The inflection points in the inverted U-shaped curve for the relationship between SII and hepatic steatosis were 399.78 for gender (1000 cells /μL)(nonlinear P< 0.01, OR=1.31 (male), 1.00 (female)) and 385.79 for age (1000 cells /μL)(nonlinear P< 0.01, OR=1.35 (18~44 years old), 1.87 (45~59 years old), 1.93 (60~ years old)).Conclusion: SII is an independent risk factor for hepatic steatosis, and this effect appears to be stronger in subjects with BMI < 28 kg/m2. The nonlinear relationship between SII and hepatic steatosis, characterized by an inverted U-shaped distribution, may serve as a reference for diagnosing and evaluating hepatic steatosis.Keywords: hepatic steatosis, systemic immune-inflammation index, inflammation, association